2005
DOI: 10.1038/sj.ijir.3901386
|View full text |Cite
|
Sign up to set email alerts
|

Male sexuality and regulation of emotions: a study on the association between alexithymia and erectile dysfunction (ED)

Abstract: Alexithymia is a multidimensional construct that describes a constellation of personality features characterised by difficulties in differentiating, identifying and communicating emotions. The purpose of the present study was to investigate prevalence of alexithymia in outpatients with erectile dysfunction (ED), both in the psychogenic lifelong type (PLED) and in the acquired one (PAED). ED severity was evaluated with the International Index of Erectile Function (IIEF) and alexithymia was measured using the It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
(28 reference statements)
1
22
1
1
Order By: Relevance
“…Therefore, personality factors impeding pharmaceutical or cognitive-behavioral management may be the hidden cause of so called drug resistance or treatment dropout. In these cases, an integrated bio-psycho-social approach, including psycho-sexual, medical and pharmacological aspects, is strongly recommended [25,62,63]. However, Extraversion as a protective factor seems to be protective in severity and management of sexual dysfunction with possible implications for clinical work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, personality factors impeding pharmaceutical or cognitive-behavioral management may be the hidden cause of so called drug resistance or treatment dropout. In these cases, an integrated bio-psycho-social approach, including psycho-sexual, medical and pharmacological aspects, is strongly recommended [25,62,63]. However, Extraversion as a protective factor seems to be protective in severity and management of sexual dysfunction with possible implications for clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed by Michetti et al, showed that alexithymia levels were significantly higher in patients with lifelong PE (2007) and ED (2006) [24,25]. The authors suggested that a high alexithymia level could contribute not only to the onset and persistence of a sexual disorder, but also to its severity [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems arguable that the quality assigned to a study by Morris and Krieger reflects a study's results more than the methodology used (see second footnote). Michetti et al (2006) reported increased alexithymia (a personality trait disorder associated with difficulty in emotional identification and expression) among men with ED problems [19]. In addition, in an empirical survey of alexithymia among circumcised versus genitally intact males (N = 300), Bollinger and Van Howe (p. 184) reported that circumcised men were, "4.53 times more likely to use an erectile dysfunction drug" than genitally intact men [20].…”
Section: Consistent With the Latter Interpretation Frisch Has Statedmentioning
confidence: 99%
“…9 Impaired cognitive processing and emotional regulation are also found in patients with various psychosomatic disorders, including male sexual and reproductive dysfunctions. [10][11][12][13] Vaginismus is a common, multifaceted sexual dysfunction defined as 'a recurrent and persistent involuntary spasm of the musculature of the outer third of the vagina that interferes with sexual intercourse' not associated with DSM IV (Diagnostic and Statistical Manual of Mental Disorders: 4th edition) Axis I psychopathological disorders.…”
Section: Introductionmentioning
confidence: 99%